MiAlbum"”A System for Home Photo Management Using the Semi-Automatic Image Annotation Approach - Liu, Wenyin; Sun, Yanfeng; Zhang, Hong-Jiang (Association for Computing Machinery, Inc., 2000)
MiAlbum© (v1.0) is a system developed at Microsoft Research China for managing family photos with the help of a semi-automatic image annotation approach. It provides functionalities to import (from scanner, digital camera, disks, PC, CD, web, etc.), label (keywords, name, place, etc.), index, browse, and search (by several means), categorize (by automatic classification into some predefined classes), manipulate (in some ways), and export (send or print) family photo images. In this demo, we show the efficiency of the semi-automatic image annotation method and its help in improving the image retrieval accuracy.